Sophocles:Oedipus Rex. - Guthrie, Tyrone; Polonsky ,Abraham (USA : Corinth.)
The land ruled by King Oedipus is plagued by ill-fortune and the people are promised relief by the gods if the slayer of the former king is apprehended and punished. This does not bode well for King Oedipus and his Queen. (Performed in masks by the Stratford, Ontario, Shakespearean Festival Players.)
Keywords: An Introduction to Oedipus; Praise the King; A Proclamation; The Prophecy of Tiresias; Creon, Traitor of friend; Rage Against Laius; Good News; No Son of Polybus; The Herdsman; Most Miserable of All Men